Evaluation of Gastroesophageal Reflux Disease and variables related with its severity in adults - Soysal, Aziz; Sağlan, Ramazan; Akbulut Zencirci, Sevil; Sağlan, Yasemin; Tırpan, Kazım; Arslantaş, Didem; Ünsal, Alaettin (Progress in Nutrition, 2019)
Gastroesophageal Reflux Disease is a chronic gastrointestinal disease that significantly reduces the quality of life and causes serious complications such as esophageal stricture, gastrointestinal bleeding or Barrett’s esophagus in some patients. This study was undertaken to evaluate some factors that are considered to be related to Gastroesophageal Reflux Disease and severity among individuals who are 40 years of age and over. This study is a cross-sectional survey conducted with individuals who were at the ages of 40 years and over who applied to 6 Family Health Centers and Family Health Centers serving in the districts of Alpu and Mahmudiye located in 3 settlements with different socioeconomic levels in Eskişehir City Center between 01 November and 30 December 2016. During the study, Individuals with symptoms of retrosternal burning and regurgitation at least 1 day a week was accepted as Gastroesophageal reflux disease in the study and the severity of the disease was assessed with the National Institutes of Health Promis Gerd Scale. Stop Bang Scale was used in assessing the risk level of obstructive sleep apnea syndrome. Among the study sample; 920 individuals were (46.8%) male and 1046 (53.2%) were female. Their ages ranged from 40 to 80 years with a mean of 56.8 ± 10.6 years. Gastroesophageal Reflux Disease was found in 18.3% (n = 360) of the study group. In our study, female gender, moderate family income status, non-steroidal antiinflammatory drug use, family history of gastroesophageal reflux disease, previous gastroesophageal reflux disease, consumption of carbonated beverage, consumption of fatty food, consumption of fermented food, presence of chronic obstructive pulmonary disease story, asthma story presence and having high risk in terms of obstructive sleep apnea syndrome were found to be important risk factors for gastroesophageal reflux disease(each; p≤0.05). Drug therapy was the most common treatment method among individuals who previously had Gastroesophageal Reflux Disease diagnosis (76.6%). In the study group; the most common Gastroesophageal Reflux Disease severity was “most symptomatic” in individuals with high risk of Obstructive Sleep Apnea Syndrome (60.6%). In this study, it was determined that Gastroesophageal Reflux Disease is an important health problem in adults. In terms of preventing gastroesophageal reflux disease and risk factors; screening should be made and health education and information services should be provided to increase the level of awareness.